Effect of Thermal Stress on Morphology in High-Performance Organic Photovoltaic Blends - Zhao, Haoyu; Prine, Nathaniel; Kundu, Soumya; Ma, Guorong; Gu, Xiaodan (JACS Au, 2024)
Thermal stress is a critical factor causing long-term instability in bulk heterojunction (BHJ) layers of organic photovoltaic (OPV) devices. This study provides direct insights into the thermal properties of Y6, PM6, and their binary blends by employing fast differential scanning calorimetry (flash DSC) to analyze their chain dynamics. The glass transition temperatures (T g) of Y6 and PM6 were measured, with Y6 exhibiting a T g of 175.2 °C and PM6 showing two T gs at 39.7 and 107.6 °C. Our findings indicate that average OPVs’ operational temperatures are lower than the blend’s primary T g of 138.2 °C. Thus, the mobility of PM6 and Y6 is not the critical factor that results in drastic drifts in the device morphology. Instead, we discovered that the crystallization of small molecules Y6 in the BHJ film at elevated operation temperatures significantly contributes to the morphological instability of the BHJ layer, based on a flash DSC isotherm crystallization study. The crystallization of the acceptor leads to severe phase separation between donors and acceptors and results in device failure. The acceptor Y6’s crystallization rate also increased when blended with donor PM6, compared to that of pure Y6 molecules. Furthermore, AFM–IR analysis of the morphology of the BHJ layer after high thermal stress of 200 °C revealed an apparent demixing of donor PM6 and acceptor Y6, revealing Y6 globules about 200 nm in diameter, with PM6 domains surrounding the Y6 regions. This crystallization-induced morphology change was later confirmed to correlate well with the device performance drop. This study offers valuable insights into the origin of BHJ layer instability in OPV devices containing nonfullerene small molecule acceptors and polymer donors. Additionally, it emphasizes the importance of addressing thermal stress to enhance the performance and durability of such devices and informs strategies for developing more stable organic solar cells.